Is Elevated Choline on Magnetic Resonance Spectroscopy a Reliable Marker of Breast Lesion Malignancy? - Prvulovic Bunovic, Natasa; Sveljo, Olivera; Kozic, Dusko; Boban, Jasmina (Frontiers in Oncology, 2021)
Background: Contemporary magnetic resonance imaging (MRI) of the breast represents a powerful diagnostic modality for cancer detection, with excellent sensitivity and high specificity. Magnetic resonance spectroscopy (MRS) is being explored as additional tool for improving specificity in breast cancer detection, using multiparametric MRI. The aim of this study was to examine the possibility of 1H-MRS to discriminate malignant from benign breast lesions, using elevated choline (Cho) peak as imaging biomarker. Methods: A total of 60 patients were included in this prospective study: 30 with malignant (average age 55.2 years; average lesion size 35mm) and 30 with benign breast lesions (average age 44.8 years; average lesion size 20mm), who underwent multiparametric MRI with multivoxel 3D 1H-MRS on a 1.5T scanner in a three-year-period. Three patients with benign breast lesions were excluded from the study. All lesions were histologically verified. Peaks identified on 1H-MRS were lipid (0.9ppm, 2.3ppm, 2.8ppm and 5.2ppm), choline (3.2ppm) and water peaks (4.7ppm). Sensitivity and specificity, as well as positive and negative predictive values were defined using ROC curves. Cohen’s Kappa test of inter-test reliability was performed (testing the agreement between 1H-MRS and histologic finding, and 1H-MRS and MR mammography-MRM). Results: Choline peak was elevated in 24/30 malignant and in 20/27 benign breast lesions. The sensitivity of 1H-MRS was 0.8, specificity 0.741, positive predictive value 0.774 and negative predictive value was 0.769. Area under ROC was 0.77 (CI 0.640-0.871). Inter-test reliability between 1H-MRS and histologic finding was 0.543 (moderate agreement) and between 1H-MRS and MRM was 0.573 (moderate agreement). False negative findings were most frequently observed in invasive lobular cancers, while false positive findings were most frequently observed in adenoid fibroadenomas. Conclusion: Although elevation of the choline peak has a good sensitivity and specificity in breast cancer detection, both are significantly lower than those of multiparametric MRM. Inclusion of spectra located on tumor margins as well as analysis of lipid peaks could aid to both sensitivity and specificity. An important ratio of false positive and false negative findings in specific types of breast lesions (lobular cancer and adenoid fibroadenoma) suggests interpreting these lesions with a caveat.